Comparison of heterogenized molecular and heterogeneous oxide catalysts for photoelectrochemical water oxidation. Issue 5 (4th April 2016) - Li, Wei; He, Da; Sheehan, Stafford W.; He, Yumin; Thorne, James E.; Yao, Xiahui; Brudvig, Gary W.; Wang, Dunwei
Abstract : Molecular and heterogeneous water oxidation catalysts improve the performance of hematite as a photoanode via fundamentally different mechanisms. Abstract : Photoelectrochemical (PEC) reactions, such as water splitting, promise a direct route for solar-to-chemical energy conversion. Successful implementations of these reactions often require the combination of catalysts with photoelectrodes. How these catalysts improve the performance of photoelectrodes, however, is not well understood, making it difficult to further improve these systems for practical applications. Here, we present a systematic study that directly compares two water-oxidation catalysts (WOCs) on a hematite (α-Fe2 O3 )-based PEC system. We observe that when a thin layer of a heterogenized molecular Ir catalyst (het-WOC) is applied to a hematite photoanode, the system's performance is improved primarily due to improved charge transfer (>2 fold), while the surface recombination rate remains unchanged. In stark contrast, heterogeneous oxide catalysts (IrO x ) improve the PEC performance of hematite by significantly reducing the surface recombination rate. These results suggest that the het-WOC provides additional charge-transfer pathways across the Fe2 O3 |H2 O interface, while IrO x and similar bulk metal-oxide catalysts replace the Fe2 O3 |H2 O interface with a fundamentally different one.